2016
DOI: 10.1155/2016/7829585
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Spanish Pain Centers: Observational Study with More than 3,000 Patients

Abstract: Chronic pain is a serious problem in Spain. This multicenter, epidemiological 3-month follow-up study investigates pain management efficacy in Spanish centers using patient satisfaction criteria. 3,414 eligible adult patients (65,6% female) with moderate to severe chronic pain from 146 pain centers were included. Patient satisfaction was assessed based onto question 18 of Spanish healthcare barometer-CSI. Pain evolution (Brief Pain Inventory-Short Form (BPI-SF) and visual analog scale (VAS)), quality of life/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
3
0
2
Order By: Relevance
“…That a greater proportion of respondents were women and the majority were working age adults is consistent with other secondary care pain surveys. Blanchard et al () and García García et al () suggesting our sample is reasonably representative. These findings are similar to cross‐sectional surveys reported in Scotland and Canada in terms of age, employment status and quality of life (Health Improvement Scotland, , Racine et al, ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…That a greater proportion of respondents were women and the majority were working age adults is consistent with other secondary care pain surveys. Blanchard et al () and García García et al () suggesting our sample is reasonably representative. These findings are similar to cross‐sectional surveys reported in Scotland and Canada in terms of age, employment status and quality of life (Health Improvement Scotland, , Racine et al, ).…”
Section: Discussionsupporting
confidence: 56%
“…Others have reported far greater improvement. ePOCC in Australia reported that 68% of respondents achieved the MIC for Pain Interference (Blanchard et al, ); a Spanish cohort study (García García et al, ) reported significant reductions in pain and improvement in quality of life. There may be good reason for these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparando el perfil de nuestros pacientes con otras series españolas estudiadas 3,4 encontramos coincidencias en datos básicos como la edad media de los pacientes derivados, unos 60 años, y su género, la mayoría pacientes mujeres. En nuestros pacientes del género femenino vemos proporcionalmente más dolores generalizados y gonalgias, y menos dolores pélvicos, de MMII, lumbalgias e inguinodinias que entre los varones (Tabla I).…”
Section: Discussionunclassified
“…11 Studies have often focused on the bivariate relationship between clinical outcomes and patient satisfaction. [12][13][14][15][16][17] The process of treating chronic low back pain has been less studied, despite the broad variety of practitioner-based interventions available to patients. 18 Perhaps this is because assessing patient satisfaction with treatment of chronic pain is complex, involving various patient populations and differing levels of satisfaction with the process and outcomes of care.…”
mentioning
confidence: 99%